2006
DOI: 10.1111/j.1600-0609.2006.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of stromal‐derived factor‐1 in the hematopoietic‐supporting activity of human mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSC) have the ability to support and maintain hematopoiesis in vitro. However, mechanisms implicated in this support are not fully characterized. In the present study, the role of stromal-derived factor-1 (SDF-1)/CXCR4 axis in the interactions between MSC and hematopoietic stem/progenitor cells (HSPC) was studied. Human bone marrow MSC were plated as feeder layers in Dexter-type long-term cultures (LTC) with human cord blood CD34(+) HSPC. Cultures were supplemented weekly with neutraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 17 publications
(19 reference statements)
2
53
0
3
Order By: Relevance
“…Besides their migratory role, these CXCR4 positive MSCs participated in neovascularization and differentiated into new myocytes. In addition, MSCs secrete or express SDF-1α [34,35] and its interaction with CXCR4 increases survival of progenitor cells [6]. SDF-1α could serve as an adhesive molecule by binding CXCR4-expressing cells to the vessel wall [36], which is consistent with our study that a high degree of CXCR4 expression is observed in the vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…Besides their migratory role, these CXCR4 positive MSCs participated in neovascularization and differentiated into new myocytes. In addition, MSCs secrete or express SDF-1α [34,35] and its interaction with CXCR4 increases survival of progenitor cells [6]. SDF-1α could serve as an adhesive molecule by binding CXCR4-expressing cells to the vessel wall [36], which is consistent with our study that a high degree of CXCR4 expression is observed in the vascular endothelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…CXCL12 signaling has been shown to regulate the balance between quiescence, cell cycle entry and apoptosis in CD34 þ hematopoietic stem cells, 48,49 and to promote cell cycle progression in CD34 þ HSPCs 50 in a contact-dependent manner in vitro. 7 Strong CXCL12 expression by CD271 þ ALP þ MSCs could be a source of abnormal survival/proliferation signaling for adjacent neoplastic CD34 þ HSPCs. CXCL12 is also involved in hematopoietic stem cell homing, 27 and isolated CD34 þ HSPCs from MDS patients are impaired in their ability to migrate toward CXCL12, 51 a finding that is associated with increased susceptibility to apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are of particular interest because they are capable of supporting self-renewing proliferation of CD34 þ hematopoietic progenitors. [5][6][7] Those purified MSCs that show multipotency are called …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, the role of these cells is not limited to their differentiation into more specialized components of the hematopoietic stroma. It has been shown for bone marrow MSCs that they can produce stromal cell-derived factor-1 [70], interact with hematopoietic cells via surface molecules (VCAM-1, cadherins, integrins and, etc. ), and regulate their proliferation and differentiation by secreting wide range of cytokines [71,72].…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%